Ab initio molecular dynamics study of the local atomic structures in monatomic metallic liquid and glass. (15th July 2015) - Zhang, J.C.; Chen, C.; Pei, Q.X.; Wan, Q.; Zhang, W.X.; Sha, Z.D.
Graphical abstract: Highlights: AIMD simulations were performed to study the atomic structures in Ta liquid and Ta MG. The dominant Voronoi polyhedra in Ta MG is 〈0,  1,  10,  2〉 instead of 〈0,  0,  12,  0〉. Our work sheds a light on the studies of the fundamental process of glass formation. Abstract: Monatomic metallic glasses (MGs), being the simplest glass formers, have been obtained successfully in recent experiments, offering unique possibilities for studying the local atomic structures in glasses. In this study, the atomic-level structures in tantalum (Ta) liquid and Ta monatomic MG have been analyzed using ab initio molecular dynamics simulations. A comparison of atomic structures in monatomic MGs and in multicomponent MGs has been made. It is found that the dominant Voronoi polyhedra in Ta monatomic MG is the distorted icosahedra 〈0,  1,  10,  2〉 rather than the full icosahedra 〈0,  0,  12,  0〉, which has been identified as the basic local structure in many multicomponent MGs. Our results reveal that the fundamental process of Ta MG formation is the formation of icosahedral type clusters, including the distorted and full icosahedra. The global atomic packing in Ta MG can be characterized by the spherical-periodic order combined with the local translational symmetry of atomic arrangements in MGs, in good agreement with previous theoretical and experimental studies on multicomponent MGs. Our findings have implications in understanding the formation of MGs, and provide a check for the existing atomic structural models proposed over the years for MGs.